Final validation of the mental health screening tool for depressive disorders: A brief online and offline screening tool for major depressive disorder - Park, Kiho; Yoon, Seowon; Cho, Surin; Choi, Younyoung; Lee, Seung-Hwan; Choi, Kee-Hong (Frontiers in Psychology, 2022)
Early screening for depressive disorders is crucial given that major depressive disorder (MDD) is one of the main reasons of global burden of disease, and depression is the underlying cause for 60% of suicides. The need for an accurate screening for depression with high diagnostic sensitivity and specificity in a brief and culturally adapted manner has emerged. This study reports the final stage of a 3-year research project for the development of depression screening tool. The developed Mental Health Screening Tool for Depressive Disorders (MHS:D) was designed to be administered in both online and offline environments with a high level of sensitivity and specificity in screening for major depressive disorder. A total of 527 individuals completed two versions (online/offline) of the MHS:D and existing depression scales, including the BDI-II, CES-D, and PHQ-9. The Mini International Neuropsychiatric Interview (MINI) for diagnostic sensitivity/specificity was also administered to all participants. Internal consistency, convergent validity, factor analysis, item response theory analysis, and receiver operating characteristics curve (ROC) analysis were performed. The MHS:D showed an excellent level of internal consistency and convergent validity as well as a one-factor model with a reasonable level of model fit. The MHS:D could screen for major depressive disorder accurately (0.911 sensitivity and 0.878 specificity for both online and paper-pencil versions). Item response theory analysis suggested that items from the MHS:D could provide significantly more information than other existing depression scales. These statistical analyses indicated that the MHS:D is a valid and reliable scale for screening Korean patients with MDD with high diagnostic sensitivity and specificity. Moreover, given that the MHS:D is a considerably brief scale that can be administered in either online or paper-pencil versions, it can be used effectively in various contexts, particularly during the pandemic.